Hubungan Antara Edukasi Anc dengan Kepatuhan Ibu Hamil dalam Kunjungan Rutin di Puskesmas Sei Lekop Kota Batam Tahun 2025 - Sevia Naldi Velangi; Mona Rahayu Putra; T. Eltrikanawati (Pusat riset dan Inovasi Nasional, 2025)
This study investigates the relationship between Antenatal Care (ANC) education and pregnant women's adherence to routine visits at Sei Lekop Public Health Center, Batam City. A quantitative, cross-sectional design was used, involving 96 pregnant women selected through purposive sampling. Data were gathered using a questionnaire assessing ANC education and visit adherence. The results showed that 50% of participants demonstrated high adherence to ANC visits, while the other 50% had low adherence. Additionally, 51% had a good understanding of ANC. Statistical analysis using the Chi-Square test revealed a significant relationship between ANC education and adherence levels (p = 0.000). The Odds Ratio (OR) of 5.343 indicates that women with good ANC education are 5.3 times more likely to attend routine visits. The study concludes that effective ANC education significantly improves adherence to antenatal care. It is recommended that healthcare providers enhance the quality of ANC education by adopting more interactive and personalized approaches and leveraging technology to reach a broader audience of pregnant women.